Asset tracking, monitoring and recovery system based on hybrid radio frequency identification and global positioning system technologies - Matshego, Itumeleng Olebogeng (Vaal University of Technology, 2021)
Tracking involves information gathering, manipulation and proving information on the location of a set item. Many single or hybrid technologies – Global Positioning System (GPS), Radio Frequency (RF), Bluetooth (BLT) or Wireless Fidelity (WiFi) – have been used to provide tracking information of an asset of interest. The use of hybrid technology in tracking assets has proven to be effective if the selection of the technologies used is done correctly. This study used a hybrid of GPS and Radio Frequency technologies to track assets of interest because of their characteristics for use inside and outside a building. In this study GPS geo-fencing was used and time interval was used to receive data from the technology. Heuristic methodology, which enabled us to divide a room into sections, was used, where testing was done in sections in a room with different types of material, such as bricks, wood or metal, and the RF signal degradation, called attenuation, was measured. A straight-line distance and a sum of distances at 30-minute intervals were calculated to determine how far the asset had travelled from the point of origin to the new position. A distance of less than 10 metres was ignored. Geofencing was used to trigger an event since it indicates that the asset has crossed the permitted boundary. An RF reader was placed at the door to identify when the asset left a building and triggered an event. A model was used for searching for a missing item in a room. The results showed that the system was able to produce two distances, one straight-line distance and the other the approximate sum distance travelled by the asset in 30-minute intervals. The RF model was able to find an asset in a room filled with different materials.
M. Tech. (Department of Information Technology, Faculty of Applied and Computer Sciences), Vaal University of Technology.
Keywords: Searcher; Global positioning system; Radio frequency tracking; Signal strength; Mobile tracking; Dissertations, Academic -- South Africa.; Global Positioning System.; Radio frequency.; Wireless communication.; Location-based services.